KEGIATAN SKREENING TUMBUH KEMBANG BALITA DI PAUD DUSUN KARANGPLOSO SITIMULYO PIYUNGAN BANTUL - Ery Fatmawati (ABDIMAS Madani, 2019)
Childhood is a very important period for growth and development. Children under the age of five need to do early detection of growth and development deviations, so that they can be detected early and can be handled with better results. Early childhood education (PAUD) in Karangploso Hamlet has not regularly carried out growth and development screenings. This community service activity aims to screen the growth and development of toddlers in PAUD Dusun Karangploso. The method used by examining toddlers using the DDST II instrument. The results of the screening for the growth and development of toddlers in PAUD Karannploso village, almost 100% of the toddlers who attended had normal growth and development. The conclusion in this activity is by implementing growth and development screening with DDST II, no one has detected a deviation in growth and development and parents know the stages of child development according to their age.